L'actionnaire de facto sous la Loi des corporations commerciales canadiennes - Demers, Robert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
The right of a de facto shareholder under the Canada Business Corporations Act of becoming a registered holder is specifically dealt with under the statute. Who can be considered as such, however, is not so clear and the rules of common law have to be considered in this context. The basis of de facto relationships in corporate law can be found in the doctrine of estoppel by conduct and the theory of the implied contract. In civil law, as estoppel is unknown, the only foundation left for such a rule is the implied contract. The following note examines these various points from the vista of civilian concepts.